Practical Column Design Guide - Nitsche, M.; Gbadamosi, R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book highlights the aspects that need to be considered when designing distillation columns in practice. It discusses the influencing parameters as well as the equations governing them, and presents several numerical examples. The book is intended both for experienced designers and for those who are new to the subject.
Planning of Distillation- and Absorption Columns --  Phase Equilibria - Bubble- and Dew Points - Flash Calculations - Activity Coefficients.- Fractionation of Binary Mixtures --  Calculation of Multicomponents-Fractionation Plants.- Extractive- and Aceotropic Distillation.- Discontinuous batch Distillation.- Steam Distillation.- Absorption- and Stripping Columns.- Fluiddynamic Dimensioning of Trays and Tray Efficiency.- Fluiddynamic Design of Random Packings / Structured Packings and Determination of the HTU-/HETP-Values.- Demister Design.
Keywords: Engineering design; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Chemistry, Technical; Engineering Design; Engineering Thermodynamics, Heat and Mass Transfer; Industrial Chemistry